Manajemen Pelayanan Publik Pada Mall Pelayanan Publik di Kabupaten Sumedang Provinsi Jawa Barat - ida Yunari Ristiani (Coopetition : Jurnal Ilmiah Manajemen, 2020)
The Local Government Program is accelerating bureaucratic reform for the development of electronic governance in information technology systems. This proves that the government is trying to improve the quality of services to the community. Law Number 25 of 2009 concerning public services as a manifestation of the demands of the community in providing quality services that are efficient and effective. This, as a breakthrough and innovation was realized by the Regulation of the Minister of Administrative Reform number 23 of 2017 concerning the implementation of Public Service Malls (MPP) in the implementation of services for the community in Sumedang Regency with a total of 360 services for 23 agencies and a total number of 88,926 visitors. Problems encountered in public service malls are related to the server that is used and the lack of public use of facilities.